2019
DOI: 10.1017/s1041610219000292
|View full text |Cite
|
Sign up to set email alerts
|

Sleep quality mediates the relationship between frailty and cognitive dysfunction in non-demented middle aged to older adults

Abstract: Objectives:Frailty is associated with cognitive decline in older adults. However, the mechanisms explaining this relationship are poorly understood. We hypothesized that sleep quality may mediate the relationship between frailty and cognition.Participants:154 participants aged between 50-90 years (mean = 69.1 years, SD = 9.2 years) from the McKnight Brain Registry were included.Measurements:Participants underwent a full neuropsychological evaluation, frailty and subjective sleep quality assessments. Direct rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 48 publications
0
20
0
1
Order By: Relevance
“…Physical mobility for our sample, which we assessed using the TUG task, was generally within agematched, normative reference values (Bohannon, 2006). Recent work has suggested that physical frailty as a composite of slow gait, muscle weakness, unintended weight loss, low physical activity, and fatigue may serve as a mediator of sleep-cognition relationships in aging (Kaur et al, 2019). By comparison, our functional assessment, being unidimensional, may have required additional measurement domains in order to detect covariate-adjusted associations with the cognitive screen used in our analysis.…”
Section: Discussionmentioning
confidence: 78%
“…Physical mobility for our sample, which we assessed using the TUG task, was generally within agematched, normative reference values (Bohannon, 2006). Recent work has suggested that physical frailty as a composite of slow gait, muscle weakness, unintended weight loss, low physical activity, and fatigue may serve as a mediator of sleep-cognition relationships in aging (Kaur et al, 2019). By comparison, our functional assessment, being unidimensional, may have required additional measurement domains in order to detect covariate-adjusted associations with the cognitive screen used in our analysis.…”
Section: Discussionmentioning
confidence: 78%
“…They sought to clarify whether sleep quality mediated associations between frailty and cognitive performance. Kaur et al (2019) found that frailty was directly associated with poorer executive function, but no other cognitive domains, and poorer sleep quality, after adjusting for covariates and accounting for multiple comparisons. Additionally, poorer sleep quality was associated with poorer executive function and processing speed.…”
mentioning
confidence: 88%
“…There appears to be bidirectional relationships between each of the three factors Kaur et al (2019) examined, which further complicates the task of understanding these relationships, but also provides more opportunities for interventions. Although the study by Kaur et al (2019) appears to be the first published study to examine sleep as a mediator between frailty and cognition, past studies have examined pieces of this relationship and have found mixed results.…”
Section: Bidirectional and Reciprocal Relationshipsmentioning
confidence: 99%
See 1 more Smart Citation
“…Kawada points out that while the use of nonparametric bootstrapping is an adequate statistical approach, there is no definite way to confirm causality. In fact, we highlighted this as a primary limitation in our manuscript (Kaur et al, 2019) and this critique applies to all observational studies. Nonetheless, we believe that our careful characterization of frailty and cognitive function in a diverse cohort of patients provides valuable data for future longitudinal studies.…”
mentioning
confidence: 98%